Explanation:
g(x) = the original function at x-2.
just means it is the same function as the original function, just moved 2 units to the right.
just think about it :
e.g.
g(3) is the same as the originated function at x=1.
g(4) is the same as the original function at x=2.
...
so, everything that happened for the original function at x, happens now for g at x+2.
therefore, again, things move 2 units to the right (positive x direction) .
that means the vertex "moves" from
(-5, 6) to (-3, 6)
the vertex of g(x) = (-3, 6)